Construction of hollow tubular Co9S8/ZnSe S-scheme heterojunctions for enhanced photocatalytic H2 evolution. (12th February 2023) - Li, Mengchao; Zhang, Donghai; Zhou, hualei; Sun, Kaiyue; Ma, Xiaohui; Dong, Mei
Abstract: Herein, ZnSe nanoparticles with good visible-light response were in-situ deposited on the surface of the hollow tubular Co9 S8 to form compact Co9 S8 /ZnSe heterojunctions via hydrothermal and solvothermal methods. This architecture is beneficial to expose more active sites due to the uniform dispersion of ZnSe particles. Under visible light irradiation, the composites at the optimum Co9 S8 amount (5 wt%) take on notably higher hydrogen evolution activity, 967.8 μmol/g/h, which is 3.1 times that of independent ZnSe (314.2 μmol/g/h). A series of tests manifested that the Co9 S8 –ZnSe heterojunction significantly promotes the separation of photo-induced electron-hole pairs, notably improves hydrogen evolution kinetics and reduces the electron transfer resistance, which is responsible for the enhanced photocatalytic activity of the composites. Furthermore, the photocatalytic mechanism of the S-scheme heterojunction was proposed based on the measured energy band potentials. This work provides a strategy in constructing inexpensive heterojunction photocatalysts for enhancing the hydrogen evolution performance. Graphical abstract: As shown in Scheme 1, the Co9 S8 /ZnSe heterojunction photocatalysts with ZnSe nanoparticles dispersed on hollow tubular Co9 S8 was constructed. Benefiting from the S-scheme heterojunction formed by the built-in electric field, improved hydrogen evolution activity and reduced electron transfer resistance, Co9 S8 /ZnSe composites exhibited excellent photocatalytic hydrogen evolution activity. Image 1 Highlights: The novel hollow tubular Co9 S8 /ZnSe heterojunction photocatalysts were constructed. The addition of hollow tubular Co9 S8 reduced the electron transfer resistance. The optimal Co9 S8 /ZnSe composites obtained a H2 evolution rate of 967.8 μmol/g/h. The S-scheme heterojunction was proposed to clarify the possible mechanism.